2003
DOI: 10.1111/j.1349-7006.2003.tb01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of p53, K‐ras, c‐kit, and β‐catenin gene mutations in sinonasal NK/T cell lymphoma in northeast district of China

Abstract: Recently we reported the different frequencies of p53 and c-kit gene mutations among sinonasal NK/T cell lymphoma (NKTCL) in Korea, north China (Beijing), and Japan, suggesting some racial, environmental, or life-style differences as a possible cause of nasal tumorigenesis. In this study, gene mutations in p53, c-kit, Kras, and β β β β-catenin gene were analyzed by polymerase chain reaction (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
1
40
1
Order By: Relevance
“…Accordingly, KIT mutations are not specific for mastocytosis. 1,[15][16][17] KIT is a known oncogene and gain-of-function mutations have been identified in systemic mastocytosis, by far the most common (480%) being found in exon 17 where a somatic point mutation, A4T in nucleotide 2468 of KIT cDNA, results in the replacement of an aspartic acid by valine at codon 816 (D816V). 18 This mutation leads to a ligandindependent constitutive activation and autophosphorylation of KIT.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, KIT mutations are not specific for mastocytosis. 1,[15][16][17] KIT is a known oncogene and gain-of-function mutations have been identified in systemic mastocytosis, by far the most common (480%) being found in exon 17 where a somatic point mutation, A4T in nucleotide 2468 of KIT cDNA, results in the replacement of an aspartic acid by valine at codon 816 (D816V). 18 This mutation leads to a ligandindependent constitutive activation and autophosphorylation of KIT.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent accumulation of ␤-catenin leads to its nuclear translocation and transcriptional activity (47). Interestingly, mutations of ␤-catenin are frequently associated with NK and T cell lymphoproliferative disorders (49,50) suggesting that ␤-catenin defects may also contribute to a loss of lymphocyte homeostasis. Our results showed that in normal NK cells, 2B4 stimulation resulted in cytoplasmic and nuclear accumulation of ␤-catenin implying that in NK cells, as in B cells, GSK-3 phosphorylation results in ␤-catenin dephosphorylation, dissociation from GSK-3, and nuclear translocation of ␤-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of p53 have been demonstrated, with variable frequencies (24 to 60%). Mutation of c-kit can also be frequently demonstrated, as far as Fas gene mutations (Hoshida et al, 2003;Shen et al, 2002). The most common cytogenetic aberration is deletion of 6q.…”
Section: Extranodal Nk/t Cell Lymphoma Nasal Typementioning
confidence: 99%